2012
DOI: 10.1039/c2mt20072d
|View full text |Cite
|
Sign up to set email alerts
|

Distinct cellular fates for KP1019 and NAMI-A determined by X-ray fluorescence imaging of single cells

Abstract: Small molecule ruthenium complexes show great promise as anticancer pharmaceuticals, but further rational development of these as drugs is stymied by an incomplete understanding of the mechanisms that give rise to markedly different biological behaviour for structurally similar species. X-ray fluorescence imaging at two incident energies was used to reveal the intracellular distribution of Ru in single human cells treated with KP1019, showing Ru localised in both cytosol and in the nuclear region. In addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 41 publications
4
69
0
3
Order By: Relevance
“…S1a and S1b). The spectra obtained after mass spectrometric analysis of KP1019 were same as observed earlier [17].…”
Section: Synthesis Of Kp1019mentioning
confidence: 90%
See 1 more Smart Citation
“…S1a and S1b). The spectra obtained after mass spectrometric analysis of KP1019 were same as observed earlier [17].…”
Section: Synthesis Of Kp1019mentioning
confidence: 90%
“…Therefore, we employed various yeast histone tail mutants to investigate the effect of KP1019. Removal of N-terminal tail of H2A (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) or H3(1-30) leads to hypersensitivity to KP1019 (Fig. 3A) suggesting that these regions of histone tails are crucial for providing resistance to this drug.…”
Section: Kp1019 Targets Histone Proteins and Chromatin Modifying Enzymentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16] Ruthenium-based complexes are some of the most promising, with reported selective potency in vitro and in vivo. [17][18][19][20][21][22] McGowan et al have synthesised a range of ruthenium metal complexes for their uses as anticancer agents. [23][24][25][26] The work published on ruthenium quinaldamides showed that under inert atmosphere conditions, the filtering over NH4PF6 yielded the ruthenium quinaldamide monomers.…”
Section: Introductionmentioning
confidence: 99%
“…Many biological properties have been attributed to ruthenium complexes including antioxidant activity [12,13] and cytotoxicity [3,9,10]. Anticancer activities of Ru(II)-DMSO complexes are known for many years and some of them are in intensively clinical trials [14,15], while Ru(II)-arene complexes have been also widely studied as anticancerogenic compounds [3,16]. Previous investigations of enzyme activities of ruthenium complexes demonstrated a slight induction of superoxide dismutase (SOD) and catalase (CAT) in the rat liver tissue [17], but also an inhibition of succinate dehydrogenase (SDH) and cytochrome oxidase (COX) activities in the brain, heart, skeletal muscle, liver and kidney of rats [18].…”
Section: Introductionmentioning
confidence: 99%